2016
DOI: 10.1016/j.molcel.2016.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Tracking of Parental Histones Reveals Their Contribution to Chromatin Integrity Following DNA Damage

Abstract: SummaryChromatin integrity is critical for cell function and identity but is challenged by DNA damage. To understand how chromatin architecture and the information that it conveys are preserved or altered following genotoxic stress, we established a system for real-time tracking of parental histones, which characterize the pre-damage chromatin state. Focusing on histone H3 dynamics after local UVC irradiation in human cells, we demonstrate that parental histones rapidly redistribute around damaged regions by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
3

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 56 publications
4
57
0
Order By: Relevance
“…The remaining single-stranded gap is filled by DNA synthesis and closed by DNA ligation (Moser et al, 2007;Ogi et al, 2010). To allow for repair despite compaction of the DNA substrate in chromatin, this multi-step process involves the temporary release of histones from damaged DNA (Adam et al, 2016) but how these chromatin rearrangements take place is not yet understood.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining single-stranded gap is filled by DNA synthesis and closed by DNA ligation (Moser et al, 2007;Ogi et al, 2010). To allow for repair despite compaction of the DNA substrate in chromatin, this multi-step process involves the temporary release of histones from damaged DNA (Adam et al, 2016) but how these chromatin rearrangements take place is not yet understood.…”
Section: Introductionmentioning
confidence: 99%
“…We propose that human cells may not have a need for HMGN1-mediated chromatin modulation to remove CPDs during TCR, because these lesions are targeted by DDB2-mediated GGR. Indeed, several studies have revealed that DDB2 mediates higher-order chromatin unfolding at sites of UV-induced DNA damage 33,34 similar to what has been proposed for HMGN1 in mouse cells 15 .…”
Section: The Strong Evolutionary Similarity (83%) Between Human and Mmentioning
confidence: 52%
“…We have shown that ANP32E increases cell survival to UVC irradiation, suggesting that ANP32E-mediated removal of H2A.Z from UVC-damaged chromatin may be of functional importance. Given that H2A.Z promotes chromatin folding in vitro (Fan et al, 2002;, the local depletion of H2A.Z could contribute to the chromatin relaxation observed at UVC damage sites (Adam et al, 2016;Luijsterburg et al, 2012). In line with this hypothesis, H2A.Z removal by ANP32E is required for histone H4 acetylation at sites of DNA doublestrand breaks (Gursoy-Yuzugullu et al, 2015).…”
Section: H2az/h2ax Exchange At Sites Of Dna Damage Repairmentioning
confidence: 84%